Endorsement and Constructive Criticism of an Innovative Online Reflexive Self-Talk Intervention - Latinjak, Alexander T.; Hernando-Gimeno, Cristina; Lorido-Méndez, Luz; Hardy, James (Frontiers in Psychology, 2019)
This study prospectively followed the experiences of skilled athletes who were involved in an innovative reflexive self-talk online intervention targeting goal-directed self-talk. Four experienced female athletes between the ages of 20 and 40 years were invited to an initial interview, a 4-week intervention, and two post-intervention interviews. Two applied sport psychologists used an online Socratic questioning approach to encourage their athletes to describe challenging scenarios, think about their use of self-talk and its effectiveness, and explore alternative self-statements that could be used in future situations. Data were multi-sourced stemming from the psychologists, athletes, and third parties (e.g., coach). Three athletes completed the intervention, whereas one athlete withdrew prematurely, mainly because the Socratic questioning approach and the online mode of delivery did not meet her preferences. From the three athlete who had completed the intervention, there was endorsement and constructive criticism of the intervention and its online delivery mode. The intervention, largely due to the accompanying raised awareness of self-talk use and refined content, seemingly benefited a range of variables including emotions, motivation, and confidence, both inside and outside of the athletes’ sports life domain. Accordingly, this new type of online intervention warrants further consideration in the literature.